A NEW ERA OF DATA VISUALIZATION: PROMPT-BASED DASHBOARDS FOR REVOLUTIONIZING BUSINESS INTELLIGENCE - Praneeth Thoutam (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
In data visualization and business intelligence, prompt-based dashboard building represents a significant shift. This thorough article examines how powerful artificial intelligence models and natural language processing are changing corporate interactions with their data. These solutions remove conventional boundaries between technical and business teams by allowing users to create sophisticated visuals using basic text commands. While evaluating their effects on operational efficiency and data democratization, this article looks at the fundamental design of well-known systems such as ThoughtSpot, Microsoft Power BI, and Looker. The technological underpinnings of prompt-based dashboards, particularly the part big language models play and their relationship with visualizing systems. This article offers a complete knowledge of both the present situation and future possibilities of prompt-based dashboard technologies using an analysis of implementation issues, best practices, and developing trends. The results imply that this technology not only speeds up insight development but also drastically alters how companies handle data analysis and decision-making procedures.